Korea as a Knowledge Economy : Evolutionary Process and Lessons Learned - Suh, Joonghae (Washington, DC: World Bank, 2012)
This report on Korea is geared towards policy makers from developing countries that are in the midst of, or are intending to, embark on the transition towards the knowledge economy. It provides pragmatic policy lessons drawn from Korea's forty-five years of knowledge-based growth. This report not only looks at the current policies and challenges of today's high income Korea, but also reviews its historical economic development since the 1960s when Korea was still a low income country. It follows Korea through the decades as it undertook an array of knowledge strategies that propelled it through the various income levels. This report therefore provides compelling policy lessons that are relevant for developing countries at different stages of economic development.